Enhancing Sociolinguistic Competence through a Digital Flipped Classroom: A Case Study in Indonesian as a Second Language Learning - Budiawan, Raden Yusuf Sidiq; Mualafina, Rawinda Fitrotul; Ulfiyani, Siti; Mukhlis (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Indonesian language instruction for foreign learners (BIPA) often places strong emphasis on grammatical proficiency while overlooking sociolinguistic competence—an aspect that is crucial for effective intercultural communication. This study aims to describe the implementation of a flipped classroom model in developing pragmatic awareness and register adaptation among BIPA learners. Using a qualitative case study approach, the research involved intermediate-level BIPA students from diverse cultural backgrounds. Data were collected through oral tests, classroom recordings, in-depth interviews, and student-generated digital artifacts. The results indicate significant improvement, particularly in register adaptation and cultural expression, each showing an average gain of 15 points. Qualitatively, learners demonstrated progress in using politeness strategies and shifting speech styles more contextually. The model created a learning space that was not only reflective and participatory, but also culturally relevant. This study recommends the integration of authentic digital content and interactive practices into future BIPA curriculum design, in order to support the formation of learners who are not only fluent, but also socially and culturally sensitive in their use of the Indonesian language.